2010
DOI: 10.1007/s11270-010-0719-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of BTEX Removal Using Granulated Surfactant-Modified Natural Zeolites Nanoparticles

Abstract: Increasing release of organic pollutants to the environment has caused one of the largest world crises for water resources. Volatile organic compounds are toxic monoaromatic pollutants of soil and water. In this research, natural zeolite nanoparticles were produced mechanically by means of a milling technique, modified using two cationic surfactants of hexadecyltrimethylammonium chloride and n-cetyl pyridinium bromide and formed as granules using a novel technique already developed by our group. The granulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…Mineral and organo-mineral sorbents are proposed as the alternative to activated carbon or organic polymers. Most studies concern the sorption of BTEX as volatile petroleum derivatives representatives [80][81][82][83][84][85][86][87]. In these papers, different organic compounds have been used for mineral surface functionalization, and the influences of pH, adsorbent dosage and initial concentration on sorption efficiency have been considered, together with the equilibrium and kinetics of sorption.…”
Section: Sorption Of Benzene and Its Derivatives Present In Aqueous Smentioning
confidence: 99%
See 2 more Smart Citations
“…Mineral and organo-mineral sorbents are proposed as the alternative to activated carbon or organic polymers. Most studies concern the sorption of BTEX as volatile petroleum derivatives representatives [80][81][82][83][84][85][86][87]. In these papers, different organic compounds have been used for mineral surface functionalization, and the influences of pH, adsorbent dosage and initial concentration on sorption efficiency have been considered, together with the equilibrium and kinetics of sorption.…”
Section: Sorption Of Benzene and Its Derivatives Present In Aqueous Smentioning
confidence: 99%
“…The authors have explored sorption capacities (q e , mg/g) of the adsorbents using standard batch technique and applied popular isotherm and kinetic models for the evaluation of possible sorption mechanisms. The concentrations of organic compounds were determined using chromatography methods such as GC-FID (Gas Chromatography coupled to a Flame Ionization Detector) [49,81,87], GC-MS (Gas Chromatograph coupled to a Mass Spectrometer) [57], HPLC (High Performance Liquid Chromatography) [80]. Table 2 summarizes the results obtained for BTEX and other organic compounds sorption on natural and modified minerals including kinetic and isotherm parameters of the best fitting.…”
Section: Sorption Of Benzene and Its Derivatives Present In Aqueous Smentioning
confidence: 99%
See 1 more Smart Citation
“…In this step for the use of nanozeolite Y powder for the adsorption of MTBE, we used a novel shaping process developed by our group that named granulation 11, 15 . In this regard sodium alginate has been used as an external template and to increase the mechanical resistance of granules a binder material such as clay was added to nanozeolite powder.…”
Section: Adsorbents Preparationmentioning
confidence: 99%
“…Parameter 1/n is the heterogeneity factor that shows the adorability of the adsorption process. KF (mg/g(dm 3 /mg)1/n) is the Freundlich constant or adsorption coeffi cient 15 . For other materials it was found that the Freundlich kinetic is the best model of describing the kinetic data for MTBE removal from water 22 .…”
Section: Freundlich Modelmentioning
confidence: 99%